Immediate implant-supported full-arch hybrid prosthesis on an edentulous patient using a barretained overdenture in the mandible: Case Report. - Contreras, Roxana (2019)
The hybrid prosthesis is a very predictable treatment option that allows patients to recover their oral functionality. It is a good alternative to conventional treatments and overdentures. The present report describes controlled an 80 year old female patient with controlled hypertension, who came for consultation with a bar overdenture with attachment holders on two external hexagonal dental implants; an immediate loading hybrid prosthesis was installed over four mandibular dental implants.